Obstetric teleconsultation by using mobile phone technology in COVID pandemic - Bharti Sharma; Minakshi Rohilla; Vanita Suri; Vanita Jain; G R V Prasad; Jasvinder Kalra; Navin Pandey (Wolters Kluwer Medknow Publications, 2023)
Introduction: Obstetrics teleconsultation is a new concept to enable health-care services in the COVID pandemic by limiting in-person visits. This study describes the methodology of mobile-based teleconsultation, preliminary findings, and the experience of the obstetricians. Material and Methods: The data of pregnant women who got registered for teleconsultation in early phase of COVID pandemic lockdown were reviewed and analyzed. A qualitative analysis was performed to assess the experience of obstetricians (consultants, senior residents, and junior residents) via an online electronic survey. Results: The majority of obstetrics teleconsultations were for routine antenatal care (75%) and fetal medicine consultation (12.3%). Out of 187 women, 29.9% were advised to continue antenatal care at local hospitals, whereas 33.6% were asked to follow up via teleconsultation. Most of the obstetricians (73.68%) felt that they were able to satisfy the pregnant women and rated the teleconsultation satisfactory. Conclusion: Obstetrics telemedicine found to be beneficial for providing routine antenatal care services via reducing physical visits and overcrowding in outpatient departments, promoting antenatal care at local hospitals, and making specialized (maternal-fetal medicine) care accessible even during COVID-19 pandemic.